Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1139/w09-099
|View full text |Cite
|
Sign up to set email alerts
|

The effects of N:P ratio and nitrogen form on four major freshwater bacterial taxa in biofilms

Abstract: Bacteria in freshwater systems play an important role in nutrient cycling through both assimilatory and dissimilatory processes. Biotic and abiotic components of the environment affect these transformations as does the stoichiometry of the nutrients. We examined responses of four major taxa of bacteria in biofilms subjected to various N:P molar ratios using either nitrate or ammonium as a nitrogen source. Fluorescent in situ hybridization was used to enumerate the Domain bacteria as well as the alpha-, beta-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
2
12
1
Order By: Relevance
“…The lack of response by any bacterial taxa examined to the nutrient amendments was unexpected, since bacterial growth has been shown to be stimulated by nutrients (Brett et al 1999). The 6-day incubation period should have been sufficient for bacterial community changes, as similar changes to nutrient amendments in our lab and others have been observed within 3-6 days (Burns and Schallenberg 1998;Fisher et al 2000;Olapade and Leff 2006;Barlett and Leff 2010). However, there are many other factors that can affect bacterial communities, including the availability and recalcitrance of carbon (Carlson et al 2002;Olapade and Leff 2005).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The lack of response by any bacterial taxa examined to the nutrient amendments was unexpected, since bacterial growth has been shown to be stimulated by nutrients (Brett et al 1999). The 6-day incubation period should have been sufficient for bacterial community changes, as similar changes to nutrient amendments in our lab and others have been observed within 3-6 days (Burns and Schallenberg 1998;Fisher et al 2000;Olapade and Leff 2006;Barlett and Leff 2010). However, there are many other factors that can affect bacterial communities, including the availability and recalcitrance of carbon (Carlson et al 2002;Olapade and Leff 2005).…”
Section: Discussionsupporting
confidence: 76%
“…Our previous work suggests that there are interactions between bacteria, nutrient stoichiometry, and form (Rubin and Leff 2007;Barlett and Leff 2010). Although correlative relationships were observed in our field survey (Rubin and Leff 2007) and other similar studies (Olapade and Leff 2004;Gao 2005), the cause and effect relationships cannot be proven.…”
Section: Introductioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Still there is a wide variation in nutrient requirements between organisms and although functional differentiation within bacterial taxa has been recognized [18][20], available techniques have not previously enabled detailed resolution of potentially ecologically coherent groups. Hence conclusions regarding nutrient limitation have been drawn for rather broad and diverse groups; for example, that Actinobacteria do not respond to carbon [21] and that Betaproteobacteria respond to ammonium but not to nitrate [22]. However, while the total community or even broad phyla might be experiencing co-limitation by N and P, the individual community members or populations could be limited by only one element [10], since taxa within a phylum are not necessarily functionally or metabolically coherent.…”
Section: Introductionmentioning
confidence: 99%
“…Organisms of the class Alphaproteobacteria, order Rhizobiales (represented by the genera Caulobacter, Shinella, and possibly Novosphingobium) were found mainly during the slower phase of degradation, when nutrient availability consisted only in more refractory compounds at limiting amounts, reflecting the group usual dominance in oligotrophic systems (Barlett and Leff, 2010). Bagatini et al (2014) also found increasing proportions of Alphaproteobacteria associated with two Cyanobacteria along cultivation time and the genus Novosphingobium has already been associated with high concentrations of recalcitrant compounds .…”
Section: Dynamics Of Bacterial Communitymentioning
confidence: 97%